(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the nutritional status and describe the quality of life (QoL) of lung cancer patients undergoing chemotherapy at Nghe An Oncology Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 110 lung cancer patients receiving chemotherapy at Nghe An Oncology Hospital in 2024. Results: The malnutrition rate among lung cancer patients based on BMI was 23.6%. According to PG-SGA, 60% of patients were malnourished or at risk of malnutrition, with 15.5% experiencing severe malnutrition (PG-SGA C). Based on the EORTC QLQ-C30 scale, the average overall health score was 49.7 ± 18.2 points. Patients with good nutritional status had significantly higher quality of life scores compared to the malnourished group (p < 0.05). Conclusion: Assessment of nutritional status in lung cancer patients indicated a high rate of malnutrition. Therefore, early screening and timely nutritional interventions are necessary to improve treatment outcomes and quality of life.